A Series of 211 Children with Probable Essential Tremor. Issue 2 (8th July 2016) - Ghosh, Debabrata; Brar, Harmeet; Lhamu, Ugen; Rothner, A. David; Erenberg, Gerald
Abstract: Background: The objective of this study was to characterize the clinical features, course, and treatment of essential tremor (ET) in children. Methods: A retrospective chart review was conducted over 25 years (1984–2011). Inclusion criteria were age <21 years and satisfying the core diagnostic criteria for ET. Primary exclusion criteria included other neurological findings, tremorogenic medications, sudden onset/stepwise progression, primary orthostatic tremor, and isolated task specificity; and secondary exclusion criteria were abnormal neuroimaging or metabolic/thyroid studies. Cases were reviewed for age, sex, family history, tremor characteristics, functional impairment, treatment, and follow‐up. Results: In total, 211 children had ET, including 130 males and 81 females. The mean ± standard deviation age was at diagnosis was 14.09 ± 5.0 years, the age of onset was 9.71 ± 5.62 years, and the age of onset was birth in 7 children. One hundred ninety‐nine children had bilateral hand tremor, 34 had asymmetry, 9 had unilateral onset but later became bilateral. Twelve children had voice tremors, 13 had leg tremors, 5 had head tremors, and 7 had trunk tremors. Tremor at rest was present in 20 children. Thirty‐five percent of the children had a family history of ET, including in a father (n = 21), mother (n = 13), brother (n = 6), sister (n = 3), and other family member (n = 28). Fifty‐five percent of patients had functional disabilities, including writing (n = 66), eating (n = 28) drinking from a cup (n = 13), typing (n = 4), playing instruments (n = 6), buttoning (n = 6), and playing (n = 3). For treatment, 33 patients received propranolol, 1 received atenolol, 13 received primidone, 3 received metoprolol, and 1 received nadolol. In total, 99 patients were followed for a mean ± standard deviation of 1.82 ± 2.21 years. If left untreated, tremor remained unchanged in 33 patients, and 7 had an apparent short‐term improvement. On propranolol, 15 of 20 patients significantly improved. Conclusions: This is the largest series to date of ET in children. The current findings indicate that onset at birth is possible, family history is less common in children than in adults, and tremor at rest is possible. Functional disability was noted in 55% of children, and 29.4% required medication.